DIGITAL-MARKETING TOOLS IN AGRICULTURAL ENTERPRISES - ZABURMEKHA, YEVGENA; HAIDUK, O.; MYKHAILOV, ARTEM (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Traditionally, most people are accustomed to consider the most effective way of advertising: advertising in print media and television, underestimating Internet advertising. Today it is becoming increasingly important to change views on product promotion on the Internet.Most small, medium and large business owners looking for options to promote goods or services turn to digital marketing tools. The Internet has made and continues to have a significant impact on the formation and development of the global information society. With the development of the Internet, approaches to business management and communication policy are changing as one of its components. The number of audiences on the Internet already exceeds a significant number of traditional media, so when forming a communication strategy, it is necessary to assess: whether Internet users are part of the target audience, how easy it is to reach it via the Internet.The theoretical aspects of the features and current trends in the development of the digital marketing system are examined in the robot. Analytical follow-up of the activity of Ltd "Biosad" was carried out. Approved methods and methods of molding and pushing products under the support of digital marketing tools.Intensive development of electronic communications is a powerful tool for selling goods and services, as well as a means of active economic and technological improvement, development of Internet sites and defines the face of the modern domestic Internet. The Internet audience is significant and is characterized by the ability to attract the attention of the target audience.A test advertising campaign was conducted on the social network Facebook, after which a decision was made to retarget. As the advertising traffic was conducted through the account, the audience of those who interacted with the company’s account during the last month was gathered.
Keywords: digital-marketing; agricultural enterprises; targeted advertising; digital means of communication